Legitimidade para agir - Ramalho, Maria Isabel (2007)
The legitimacy to act, condition of the action also denominated legitimatio ad causam, it is an indispensable quality that makes it possible the author and the defendant can take part in the active and passive poles of the process, and it is expressly demanded by the 3rd article of the current Code of Civil Process. The proposal of the action for or against the illegitimate part results in the extinction of the process, creating the phenomenon of the action lack. By configuring matter of public order, to denounce the absence of the legitimacy is not linked to the dispositive principle, it is not covered by any preclusion type, it has been authorizing pronouncement ex officio and it escapes to the effects of the thing judged material, justifying the choice of the theme the possibility of studying that content, objective of the present theory. The research goes through the general theory of the process, allowing brief summary of the controversy on the juridical nature of the right of acting, elaborated from the civilian theories and coming to the modern conception of the action right as constitutional warranty. It studies about the conditions of admissibility to regulate exercising with views to the obtaining of pronouncement of merit, such as, juridical possibility of the request, procedural interest and legitimacy to act. It also focuses on the doctrine divergence concerning to the nature of those conditions (preliminary or merit?), the control of its existence, the nature of the decisions that recognize its absence and the forms of conceivable impugnation. This work also deals with the definition and classification of the legitimacy ad causam, with foundation in pointed criteria in specific doctrine, showing special consideration to the study of the procedural substitution, species of extraordinary legitimacy whose incidence demands legal prediction in the Brazilian law. It finally analyses the treatment granted to the legitimacy in the knowledge processes (in the appeal and incident scopes), in the execution and in the precautionary procedure as well as in the collective actions